The Analysis of Electromagnetic Field Impact of Mobile Communication Antennas: The Case Study of Lombardy, Italy - Virtyt Lesha; Besmira Kuqi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The analysis of electromagnetic field of mobile communications antennas is a very widespread method in the technology of telecommunications systems and it is closely connected with the laws in force of E.U regarding impact of these waves on human health. It makes possible the assessment of the field of electromagnetic waves created by cellular antennas. The study in question in this paper deals with a specific case of a project implemented in Bergamo, Italy. In this project, it was made possible, through the program AutoCad and EMLab simulator, the designing of buildings within a radius of 150 m from the tower where the antennas stay and the simulation the electromagnetic waves that penetrate in the building in question. This study treats the case, where current electromagnetic waves penetrate through areas where people stay for more than 4 hours, and where the size of the electromagnetic wave magnitude is bigger than 6V / in conflict with the current EU law on the issue of electromagnetic non-ionizing waves. Once the problem is evidenced, we have given the necessary recommendations to avoid as much as possible the penetration of electromagnetic according the directives mentioned above.
Keywords: L96; 330; antenna; electromagnetic field; simulator; technology; mobile communication; law; non-ionizing; wave